2021
DOI: 10.3389/fgene.2021.773597
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Diversity of the Maize ZmCNR13 Gene and Association With Ear Traits

Abstract: The maize (Zea mays L.) ZmCNR13 gene, encoding a protein of fw2.2-like (FWL) family, has been demonstrated to be involved in cell division, expansion, and differentiation. In the present study, the genomic sequences of the ZmCNR13 locus were re-sequenced in 224 inbred lines, 56 landraces and 30 teosintes, and the nucleotide polymorphism and selection signature were estimated. A total of 501 variants, including 415 SNPs and 86 Indels, were detected. Among them, 51 SNPs and 4 Indels were located in the coding re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…NOD encodes a PLAC8 domain and is structurally related to genes including CELL NUMBER REGULATOR 1 ( CNR1 ) in maize and FW2.2 , a gene responsible for a major quantitative trait locus for fruit weight in tomato (Frary et al., 2000 ; Guo et al., 2010 ). Moreover, a recent study found that some polymorphisms in NOD alleles among maize genotypes are significantly associated with yield‐related traits in ear morphology (Zuo et al., 2021 ). Thus, NOD and NOD‐like proteins play crucial roles in agricultural species, and they could even be useful targets for plant breeders (Beauchet et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…NOD encodes a PLAC8 domain and is structurally related to genes including CELL NUMBER REGULATOR 1 ( CNR1 ) in maize and FW2.2 , a gene responsible for a major quantitative trait locus for fruit weight in tomato (Frary et al., 2000 ; Guo et al., 2010 ). Moreover, a recent study found that some polymorphisms in NOD alleles among maize genotypes are significantly associated with yield‐related traits in ear morphology (Zuo et al., 2021 ). Thus, NOD and NOD‐like proteins play crucial roles in agricultural species, and they could even be useful targets for plant breeders (Beauchet et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%